Efektivitas Media Pembelajaran Interaktif Berbasis Teknologi Dalam Meningkatkan Pemahaman Konsep Ipa - Taroreh, Lidya H. J. (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2024)
This study aims to analyze the effectiveness of technology-based interactive learning media in improving students' understanding of science concepts. Technology-based learning media, such as virtual simulations and interactive applications, are designed to support more engaging and participatory learning. The research method employed is an experimental design with a pretest-posttest control group design. The research subjects consisted of junior high school students divided into two groups: an experimental group using interactive learning media and a control group using conventional methods. The results showed that the use of technology-based interactive learning media significantly improved students' understanding of science concepts compared to conventional teaching methods. These findings suggest that integrating technology into science education can be an effective strategy to address students' difficulties in understanding abstract concepts. This research is expected to contribute to the development of innovative learning media relevant to the needs of modern education.